How the Rise of Teleworking Will Reshape Labor Markets and Cities - Toshitaka Gokan; Sergei Kichko; Jesse A. Matheson; Jacques-Francois Thisse (Center for Economic Studies and ifo Institute (CESifo), 2022)
In recent years the land-rent gradient for the city of London has flattened by 17 percentage points. Further, teleworking has increased 24 percentage point for skilled workers, but much less for unskilled workers. To rationalize these stylized facts, we propose a model of the monocentric city with heterogeneous workers and teleworking. Skilled workers, working in final goods production, can telework while unskilled workers, working in either final goods or local services production, cannot. We show that increased teleworking flattens the land-rent gradient, and eventually skilled workers move from the city center to the city's periphery, fundamentally changing the city structure. The increased teleworking has implications for unskilled workers who move from the local services sector into final goods, leading to greater wage inequality between skilled and unskilled workers. The model is extended to two cities which differ in productivity. Teleworking allows skilled workers of the more productive city to reside in the less productive city where housing is cheaper. This increases housing prices in the less productive city, relative to the more productive city, and has implications for unskilled workers in both cities. We provide empirical evidence from housing prices in England which is consistent with this result.
Keywords: J60; R00; 330; telecommuting; working from home; gentrified cities; doughnut cities; inter-city commuting